Household Size and Access to Education in Rural Burundi: The Case of Mutaho Commune - Ndayishimiye Bosco; Manirakiza René; Kakuba Christian; Sindayihebura Jean François Régis; Barankanira Emmanuel (De Gruyter, 2024)
While education is recognized as a fundamental human right and an important factor in improving economic and social conditions, child schooling rates in Burundi show that there are still children of school-age who are not attending school and those who drop out very prematurely. This scientific study aims to highlight the relationship between household size and access to education in Mutaho commune (rural Burundi) by documenting the socio-demographic factors of the head of household likely to influence the schooling status of children aged 7-17. The hypothesis put forward in this study is that children's schooling is influenced by household size. Data from a survey of 215 households in the Mutaho commune were analyzed using binomial logistic regression. The analysis shows that a large household size (OR = 5.463; p < 0.05; 95% CI: 1.311-22.771) is negatively associated with the education of children aged 7-17 living in Mutaho commune. Reducing fertility should be an integral concern for all those involved in the fields of population, education, and development.